Learning health systems: A review of key topic areas and bibliometric trends. Issue 1 (18th March 2021) - Pomare, Chiara; Mahmoud, Zeyad; Vedovi, Alex; Ellis, Louise A.; Knaggs, Gilbert; Smith, Carolynn L.; Zurynski, Yvonne; Braithwaite, Jeffrey
Abstract: Introduction: The emergent field of learning health systems (LHSs) has been rapidly evolving as the concept continues to be embraced by researchers, managers, and clinicians. This paper reports on a scoping review and bibliometric analysis of the LHS literature to identify key topic areas and examine the influence and spread of recent research. Methods: We conducted a scoping review of LHS literature published between January 2016 and May 2020. The authors extracted publication data (eg, journal, country, authors, citation count, keywords) and reviewed full‐texts to identify: type of study (empirical, non‐empirical, or review), degree of focus (general or specific), and the reference used when defining LHSs. Results: A total of 272 publications were included in this review. Almost two thirds (65.1%) of the included articles were non‐empirical and over two‐thirds (68.4%) were from authors in the United States. More than half of the publications focused on specific areas, for example: oncology, cardiovascular care, and genomic medicine. Other key topic areas included: ethics, research, quality improvement, and electronic health records. We identified that definitions of the LHS concept are converging; however, many papers focused on data platforms and analytical processes rather than organisational and behavioural factors to support change and learning activities. Conclusions: The literature on LHSs remains largely theoretical with definitions of LHSs focusing on technical processes to reuse data collected during the clinical process and embedding analysed data back into the system. A shift in the literature to empirical LHS studies with consideration of organisational and human factors is warranted.